ZONASI SITE EFFECT DAN ANALISIS BAHAYA PENGUATAN GEMPA MENGGUNAKAN METODE DSHA UNTUK MENENTUKAN PGA DI KABUPATEN SUMBA BARAT DAYA - Soulthan Salahudin Al Ayubi; Karyanto Karyanto; Nandi Haerudin; Syamsurijal Rasimeng; Rahmat C Wibowo (Universitas Mataram, 2020)
Southwest Sumba Regency is located in the Banda Arc area. Its position which is very close to the subduction area in the south of Indonesia caused a lot of tectonic activity and earthquake hazard. The arrangement of alluvium, coral, and thick deposits on the island of Sumba makes it prone to earthquake strengthening. Zoning of soil characters using site effects and DSHA method was carried out to determine the danger level of strengthening the Southwest Sumba Regency. Zoning of the site effect soil character uses microtremor data which is correlated with seismic hazard analysis to obtain the PGA values on bedrock and ground surface using the closest earthquake source. The area is dominated by Class 2 and 3 lands (f0 worth 1.333 - 5 Hz) according to the Kanai Classification (1983), with an amplification predominance of 3.8-8.3 times. This indicates that the research area is dominated by thick sediment deposits. The PGA value obtained from the DSHA method is known that Southwest Sumba Regency has a PGA soil of 0.075-0.19 g and a bedrock PGA of 0.067-0.085 g using earthquake record data in Sumba Subduction and Timor Subduction. With PGA estimation, it is known that the level of earthquake disaster vulnerability is high, located in the south of Southwest Sumba Regency which is suspected to be composed of thick sediments and close to the Sumba Subduction and Timor Subduction.Keywords: Site effect, predominant frequency, amplification, earthquake, DSHA, PGA